2016
DOI: 10.7150/thno.14744
|View full text |Cite
|
Sign up to set email alerts
|

Towards Personalized Treatment of Prostate Cancer: PSMA I&T, a Promising Prostate-Specific Membrane Antigen-Targeted Theranostic Agent

Abstract: Prostate-specific membrane antigen (PSMA) is a well-established target for nuclear imaging and therapy of prostate cancer (PCa). Radiolabeled small-molecule PSMA inhibitors are excellent candidates for PCa theranostics—they rapidly and efficiently localize in tumor lesions. However, high tracer uptake in kidneys and salivary glands are major concerns for therapeutic applications. Here, we present the preclinical application of PSMA I&T, a DOTAGA-chelated urea-based PSMA inhibitor, for SPECT/CT imaging and radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
100
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 45 publications
(45 reference statements)
3
100
0
Order By: Relevance
“…We did not expect the occurrence of nephrotoxicity, as we are well below the renal toxicity threshold of 23 Gy. A similar radioactive dose to kidneys using 177 Lu-PSMA I&T did not induce any late renal toxicity (41). The therapeutic effect obtained with [ 131 I]-2Rs15d was less pronounced compared to that obtained with [ 177 Lu]DTPA-2Rs15d (21), but in the latter, we administered about 150 MBq resulting in a recalculated absorbed dose to tumor of 40 Gy, compared to 15 Gy (at 46.25 MBq) to tumor in this study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We did not expect the occurrence of nephrotoxicity, as we are well below the renal toxicity threshold of 23 Gy. A similar radioactive dose to kidneys using 177 Lu-PSMA I&T did not induce any late renal toxicity (41). The therapeutic effect obtained with [ 131 I]-2Rs15d was less pronounced compared to that obtained with [ 177 Lu]DTPA-2Rs15d (21), but in the latter, we administered about 150 MBq resulting in a recalculated absorbed dose to tumor of 40 Gy, compared to 15 Gy (at 46.25 MBq) to tumor in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Based on dosimetry calculations, we could increase the cumulative activity administered by twofold, without the need for extra kidney-protective measures such as coinjection with Gelofusin and/or positively charged amino acids, which could theoretically lead to a tumor absorbed dose of 30 Gy. Future long-term studies of renal toxicity will be required (41). In addition, therapeutic efficacy of [ 131 I]-2Rs15d will be further assessed in the trastuzumab-resistant JIMT-1 model, which is targetable by 2Rs15d but not by trastuzumab.…”
Section: Discussionmentioning
confidence: 99%
“…The biodistribution of CTT1403 showed a tumor:kidney ratio of ~1 at time points longer than 4 h. For comparison, for the 211 At-labeled urea-based agent, the kidney uptake was 3-4 fold greater than that of the tumor, and long-term toxicity studies confirmed that the high kidney uptake was dose-limiting 63. For PSMA-targeted therapy, co-administration of 2-PMPA is a documented strategy to improve the tumor:kidney ratio 60, 65 and may effectively complement the addition of the albumin-binding moiety as shown in our blocking study. Chatalic et al compared therapy with 100 MBq of 177 Lu-PSMA I&T (29 MBq CTT1403 was used in this study) with and without 2-PMPA in PSMA-transfected LS174T colorectal tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%
“…[2] A number of small molecules targeting the extracellular domain of PSMA with exceptional affinity and specificity have been developed. [3,4] The TheraP study has been designed to investigate the efficacy of the [ 68 Ga] Ga-PSMA-11 / [ 177 Lu]Lu-PSMA-617 theranostic pair. For this study, the radiosynthesis and formulation of [ 177 Lu]Lu-PSMA-617 was automated on an iPHASE MultiSyn radiosynthesizer.…”
Section: Discussionmentioning
confidence: 99%